Design of Incubation Environment Detection System Based on STM32 Single-chip Microcomputer - Shi, Ruihua (Scientific Journal of Technology, 2025)
This design focuses on the "Incubation Environment Detection System" and proposes a system that uses STM32 microprocessor as the microprocessor controller. It can collect real-time temperature and humidity data in the incubation room to obtain the hatching status of chicks. During the system’s operation, it can control the temperature and humidity of the incubation room through fans and incandescent lamps. When the system detects that the temperature and humidity parameters in the incubation room exceed the warning value, it will immediately start the fan for cooling and dehumidification. When the temperature is too low, it will control the temperature through incandescent lamps. The system will display the system data through a high-definition LCD screen, and at the same time, the data can be sent to a mobile APP for display through a WIFI module. This system is dominated by STM32 microprocessor chips in terms of core control, and corresponding driver circuit parts have been designed according to the requirements of various expected functional indicators. In order to facilitate the optimization and improvement of the design results, this graduation project underwent operational debugging. Through extensive testing work, defects were identified and analyzed for optimization. Ultimately, this model of incubation environment detection and control system can operate efficiently and meet the expected functional requirements.